INVESTIGATING THE KEY FACTORS INFLUENCING GROUNDWATER QUALITY IN SUPAUL DISTRICT, BIHAR: A DETAILED ASSESSMENT OF DRINKING WATER - Bartoshuk, BaSimpi; Agarwal, Kumar (International Journal of Allied Sciences (IJAS), 2023)
Life depends on water, and the aim of this study is to evaluate the drinking water quality in Supaul district of Bihar. Water samples were collected from ten tubewells and ten wells across five villages in the district. The research focused on examining various physicochemical properties, such as pH, electrical conductivity, free carbon dioxide, total alkalinity, total hardness, dissolved oxygen, biological oxygen demand, and chemical oxygen demand. The findings indicated that all the parameters met the permissible standards set by the Bureau of Indian Standards, except for chemical oxygen demand, which necessitates further research.